The Phenomenon of Trombley-Brennan Terminal Tissue Injury in a Neonate: A Case Study. (April 2020) - Jacob, Ani; Grabher, Deborah
Abstract : Background: Trombley-Brennan terminal tissue injury (TB-TTI), also known as skin failure, was first identified in 2009 among critically ill adults receiving palliative care. Identification of this skin injury can be misinterpreted as a pressure ulcer. However, this phenomenon is now accepted as an early sign of impending death among critically ill adults. Clinical Findings: This case study describes TB-TTI in a terminally ill infant in a neonatal intensive care unit evidenced by intact, 2-cm oval skin discoloration on the lateral side of both knees with rapid progression in size. Primary Diagnosis: TB-TTI was identified on the day of death in an infant with a primary diagnosis of hypoxic-ischemic encephalopathy born at 32 weeks' gestation. Interventions: The neonatal intensive care unit (NICU) team mobilized the NICU advanced care team, institution's ethical council, and "Team Lavender" to provide infant comfort measures and emotional support to the family and care givers. Outcomes: Infant death occurred 8 hours after TB-TTI was identified. Practice recommendations: To our knowledge, this case study of TB-TTI in a terminally ill neonate in the NICU has not been previously described in the neonatal or pediatric population. Early recognition of the phenomenon can enable the healthcare team to provide timely emotional, spiritual, and psychosocial support to the family and allow time to "be present" with the infant at "end of life." Future work should explore additional signs of TB-TTI and the occurrence rate.